Caddie Woodlawn - Brink, Carol Ryrie, 1895-1981.; Hyman, Trina Schart (Old Tappan, NJ : Simon & Schuster, 1973)
The adventures of an eleven-year-old tomboy growing up on the Wisconsin frontier in the mid-nineteenth century.
Accelerated Reader AR
Newbery Medal, 1936.
Keywords: Frontier and pioneer life -- Wisconsin -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Newbery Medal; Wisconsin -- Juvenile fiction; Historical fiction